STRUKTUR KOMUNITAS MANGROVE DI TELUK POTON BAKO SEBAGAI BUKU PANDUAN UNTUK PEMANTAPAN KONSEP EKOSISTEM PADA GURU BIOLOGI SMA DI KABUPATEN LOMBOK TIMUR - Safnowandi, Safnowandi (Jurnal Ilmiah IKIP Mataram, 2021)
Poton Bako Bay seashore Jerowaru Village Jerowaru District East Lombok Regency has natural resources which are abundant, one of the natural resources contained therein are mangrove forests. Mangrove’s in here from time to time have decreaseddue tohuman actions irresponsible. Syllabus subjects for high school biology class X in the second half, one of which out line discusses diversity and ecosystem conservation effortsand sustainable useof natural resources. The community structure of mangrove canbe used particularly by high school biology teacherin East Lombok. Such information can bepackaged in the form of instruction alguideÂ book contains material that can help teachers and students in learning the structure of mangrove communities. Comparative descriptive research and development research. Mangrove species found are Rhizophora stylosa, Rhizophora mucronata, and Sonneratia alba. Abundance of mangrove plants are found on sandy substrate 521 people, while 328 people muddy substrate. Diversity of mangrove plants on sandy substrates 0.90 and 0.76 muddy substrate. Evenness mangroves on sandy substrates 0.20 and 0.18 muddy substrate. As for the dominant population in a community can be known based on the critical value. The most dominant species is Rhizophora stylosa, with important values on sandy substrate amounted to 159.20% and 149.88% amounting muddy substrate. Summative evaluation results format guide book by expert biological material sreceivedan average score of4(included inboth categories), by the development of teaching material sexpertgotan average score of4(included inboth categories), and by teachersas users of the product got a score of average the average 4 (including inboth categories).